Синхронизация потоков данных в многоканальных системах ЦОС с перестраиваемой структурой - Sheik-Seikin, A. N. (PE "Politekhperiodika", Book and Journal Publishers, 2012)
The special features of the synchronization of data flows in the multichannel DSP systems with different architecture are examined. It is shown that in a number of cases the timing system can be realized in the form of a totality of local systems, which makes it possible to lower the level of the interferences created by them and to simplify their realization due to the reduction of the number of global connections. The method of the integrated assessment of the realization efficiency (equipment expenditures) of the projected system taking into account the complexity of timing system is proposed.